Influence of the turbulence conditions of crosswind on the aerodynamic responses of the train when running at tunnel-bridge-tunnel. Issue 229 (October 2022) - Yang, Weichao; Yue, Huan; Deng, E.; Wang, Youwu; He, Xuhui; Zou, Yunfeng
Abstract: High-speed trains (HSTs) often encounter crosswinds with complex pulsating components when running at a tunnel-bridge-tunnel section (TBTS), and their running safety may deteriorate sharply due to the complex terrain conditions in mountainous areas. This study aims to discuss the influence relationship of different turbulent conditions of the crosswind on the aerodynamic response of the HST passing through the TBTS. On the basis of the measured wind field data of a typical TBTS site, the pulsating wind field is numerically reconstructed by large eddy simulation, and the influence of the incoming flow dimension, the turbulence intensity and the average wind speed on the aerodynamic loads of the HST running at the TBTS are analysed. The corresponding influence mechanisms are explained in terms of the pressure distribution and flow field structure of the HST. The influence of the loading dimension of aerodynamic load and incoming turbulence intensity on the dynamic response index of the train body and wheel-rail contact is further discussed by establishing a wind-vehicle-bridge-tunnel coupling dynamic calculation model. The main conclusions are as follows: At the TBTS, the 1D pulsating incoming flow simulation scheme can be used rather than the 3D incoming flow scheme in calculating the aerodynamic response of the HST. The influence of the incoming turbulence intensity on the aerodynamic load of the HST is mainly reflected at the bridge section (BS), The fluctuation extent of the aerodynamic load of the HST increases with the increase in the turbulent intensity of the incoming flow. When the incoming flow turbulence intensity increases from 0 to 0.09, at the BS, the pitching acceleration of the train body and the vertical contact force of the wheel-rail on the leeward side increase by 18% and 16%, respectively. The average wind speed of the incoming flow has an important effect on the aerodynamic load of the HST, especially the head train, running at the TBTS. A linear positive correlation is found between the average wind speed of the incoming flow and the corresponding change amplitude of the aerodynamic load coefficient of the head train. When the HST runs at the TBTS, the five aerodynamic loads should be loaded in the calculation process of the aerodynamic response index of the HST, and the calculated wheel-rail response results are conservative when only two aerodynamic loads are applied to the train body. Highlights: The instantaneous vortex structures around HST running at the TBTS are investigated based on the LES method. The pulsating wind field is reconstructed based on field tests. A set of formulas are given to quantitatively describe the relationship between aerodynamic loads and average wind speeds. The influence mechanism of incoming turbulence conditions on the aerodynamic response of the HST at the TBS is revealed. The fluctuation of the HST aerodynamic load increases with the increase in the turbulent intensity of the incoming flow.